Rhodium(III)-Catalyzed C–H Activation of Phenylazoles toward C–N Bond Cleavage of Diazabicyclic Olefins: A Facile Access to Mono- and Biscyclopentenyl-Functionalized Aza-Heteroaromatics - Prakash, Praveen; Aparna, P. S.; Jijy, E.; Santhini, P. V.; Varughese, Sunil; Radhakrishnan, K. V. (Synlett, 2014)
A [RhCl2Cp*]2-catalyzed stereoselective C–N bond cleavage of diazabicyclic olefins via C–H activation of phenylazoles in the presence of an acetate source is described. The developed method provides an easy access to biologically significant mono- and biscyclopentenyl- and alkylidenecyclopentenyl-functionalized aza heteroaromatics.
Keywords: rhodium; C–H activation; bicyclic olefin; cyclopentene; aza heteroaromatic